The influence of drug therapy for obstructive sleep apnoea on couple life. Qualitative study grounded theory. (14th October 2021) - Rosa, D; Amigoni, C; Villa, G; Albanesi, B; Bonetti, L; Lombardi, C; Perger, E; Parati, G
Abstract: Background: Obstructive sleep apnoea (OSA) is characterised by the collapse of the upper airway during sleep, which determine intermittent hypoxia and sleep fragmentation leading to snoring, impaired cognitive function, excessive daytime sleepiness, and cardiovascular impairments. These disorders have a significant impact on the quality of life and health of both patient and partner, determining stress and frustration also to the couple relationship, and to the workplace. Although the gold standard of treatment for OSA is the use of continuous positive airway pressure (CPAP), many patients find it uncomfortable both for them and for their partners (difficulty in partner intimacy, fear of disturbing their partner's sleep) with consequent low adherence to treatment in about 50% of OSA patients. For these reasons, efforts to develop drug therapies for the treatment of OSA have been ongoing for at least 20 years. Recently, we conducted a randomized controlled trial (RCT) in Italy to test the combination of reboxetine (a noradrenergic agent) and oxybutynin (an antimuscarinic) for OSA treatment with promising results. The aim of this study is to understand how OSA drug therapy has influenced couples' life. Methods: The study was conducted from February to March 2020 by the research nurse who participated during the trial. We interviewed 11 patients participating in the pharmacological RCT and 7 partners. The data analysis was conducted in order to collect the subjects' answers in categories, and to identify a core category as the central element for the explanation of the process. Results: Interviews permitted to extrapolate 6 main categories and the relative subcategories for patients: 1) OSA: unconscious danger; 2) OSA and couple life (subcategories: sleepiness and nervousness, lack of sleep); 3) transitory situations; 4) drug therapy and couple (subcategories:change in intimacy and sleep quality); 5) motivation to help others (subcategories: therapy recommended for everyone; intention to continue); 6) partner awareness helps in adherence to therapy (subcategories: partner as caregiver, presence and proximity, partner support). While for partners, 7 main categories and the relative subcategories emerged: 1) apprehension and concern for the partner; 2) repercussions on daily life (subcategorie: discomfort); 3) OSA and the couple's lives; 4) drug therapy and couple; 5) support during therapy (subcategorie: before therapy, during therapy); 6) changes during drug therapy; 7) recommended therapy (subcategories: helping others, partner support). "The OSA is our problem" was the core category of the study that linked the categories together. Conclusions: Drug therapy is well embraced by both patients and partners as it allows the couple to recover intimacy during sleep and in daily life. The results of this study provide useful information on the need to involve the partner in order to promote adherence to therapy. FUNDunding Acknowledgement: Type of funding sources: None.